Estrutura e produtividade de capim-tanzânia submetido a diferentes frequências de desfolhação - MACEDO, Vitor Hugo Maués (Universidade Federal do Pará, 2017)
The objective of the present study was to evaluate the effect of different frequencies of defoliation at fixed periods on the structural and productive characteristics of Tanzania grass (Panicum maximum) under Am climate conditions in 2014. The experimental design was in complete randomized blocks with six treatments corresponding to six frequencies of defoliation (14, 21, 28, 35, 42, and 49 days) and five repetitions. The data was submitted to regression analysis. The light interception (LI) increased (P <0.05) in an asymptotic way with increasing rest periods. The maximum light interception was 98% and occurred at 42 days of regrowth. The leaf area index (LAI) and the dry matter accumulation increased (P <0.05) linearly varying from 3.6 to 7.1 and from 880.3 to 4051.7 kg.ha-1 of forage dry matter in the frequencies 14-49 days, respectively. The height ranged 44-119 cm at frequencies 14-49 days, respectively. The frequency of defoliation at 95% LI is related to the rest period of 29 days, where the Tanzania grass canopy presented around 63 cm height, critical LAI of 5.1, and forage dry matter accumulation of 2,160 kg ha-1.